An A Priori Estimate for the Modulus of Continuity of a Generalized Solution of a Parabolic Equation of Divergent Form with Degeneracy - Verba, I. I.; Kolody, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study parabolic equations of divergent form with degeneracy λ(x) with respect to the space variable. We establish an a priori estimate of the Hölder norm of generalized solutions. The problem is considered in parabolic cylinders having a special time dimension induced by the degeneracy λ(x).